Cross-Coupling Reactions Between Alkynyl Metals and (Pseudo)Halides Induced by Earth-Abundant Transition Metals (Mn, Fe, Co, Ni, Cu) - Cossy, Janine (Synthesis, 2025)
In this review, we describe the synthesis of substituted alkynes by C–C bond formation, using cross-coupling reactions between alkynyl metals (alkynyl Grignard reagents and alkynyl zinc derivatives) with (pseudo)halides, catalyzed by abundant and inexpensive transition metals such as manganese, iron, cobalt, nickel, and copper. These cross-coupling reactions are chemo- and stereoselective.
Keywords: Alkynyl Grignard reagents; Alkynylzinc derivatives; (Pseudo)halides; Cross-couplings; Transition metals